Optimization of Binluh by Bhabinkamtibmas in Preventing Drug Abuse in the Jurisdiction of Gresik Police - Gymnastiar, Firdaus Ramdhan (Advances in Police Science Research Journal, 2024)
From 2021 to 2022, drug cases in the Gresik Police jurisdiction were significally increased. Within one year, the cases increased to 61 cases. The aim of the research was performance of binluh counseling by Bhabinkamtibmas in efforts to prevent drug abuse in Gresik Police Juridiction and to determine the optimization of the binluh Bhabinkamtibmas of the Gresik Police Binmas Unit in tackling drug abuse in the jurisdiction of the Gresik Police. This research used the concept of optimization, the concept of coaching and counseling, the concept of social security and security, the concept of crime prevention, the concept of fraud, and the concept of social security. Meanwhile, the theories used are process management theory, SWOT analysis method and organizational resource theory. The approach in this research is qualitative with the type of field research. The informants in this research were the Gresik Police Chief, the Head of the Human Resources Section of the Gresik Police, the Head of the Gresik Police Community Guidance Unit, a member of the Gresik Police’s Community Security and Order, and drug abusers. Data collection techniques in this research were interviews, observation, and document study. The data analysis techniques used were data collection, data reduction, data presentation, and conclusion. Optimizing the implementation of guidance and counseling on drug abuse for the jurisdiction of the Gresik Police is yet to be optimal, due to the lack of sufficient Bhabinkamtibmas members, as well as the lack of facilities and infrastructure, which prevents the performance of Gresik Police members from being optimal. However, on the other hand, the implementation of Binluh by Bhabinkabtibmas is right on target and the implementation and documentation are going well because there is a budget every three months that supports binluh optimization activities by Bhabinkamtibmas in the jurisdiction of the Gresik Police.